A Paradigm Shift in Osteoporosis Screening with AI: The Canadian Experience with Rho - Syme, Catriona; Setia, Pardaman; Bilbily, Alexander; Cicero, Mark (Osteologie, 2025)
Osteoporosis, characterized by reduced bone mineral density (BMD), affects 200 million people worldwide. Osteoporosis-associated deterioration of bone quality increases an individual’s risk of a fragility fracture. After a first (primary) fracture, fracture risk increases considerably. Reduction of primary fragility fractures requires patient awareness of risk factors and initiation of strategies to optimize bone health. A novel machine learning-powered medical device, Rho™, analyzes routine X-rays, being acquired for any clinical indication, and alerts a radiologist at time of reporting the x-ray if the patient is at risk of having low BMD. By including the opportunistic finding in their X-ray report, the radiologist can prompt the often-overlooked clinical fracture risk assessment. In Canada, Rho has prospectively screened over 250,000 patients as part of routine care. In studies that have assessed outcomes of Rho findings, many patients are newly diagnosed with osteoporosis or elevated fracture risk. Once CE marked, Rho has the potential to reduce the burden of osteoporotic fractures on patients and the German healthcare system.
Keywords: bone mineral density; opportunistic screen; machine learning; x-ray